Oral antibiotics perturbation on gut microbiota after prostate biopsy - Li, Joseph Kai Man; Wang, Lynn Lin; Lau, Becky Su Yan; Tse, Ryan Tsz Hei; Cheng, Carol Ka Lo; Leung, Steven Chi Ho; Wong, Christine Yim Ping; Tsui, Stephen Kwok Wing; Teoh, Jeremy Yuen Chun; Chiu, Peter Ka Fung; Ng, Chi Fai (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction The use of antibiotics may induce the changes in gut microbiota. Previous studies have shown conflicting results on whether the changed gut microbiota by antibiotics can be recovered. Our study aims to investigate whether the gut microbiota could be recovered after a single dose of oral co-amoxiclav before transrectal ultrasound-guided transperineal prostate biopsy (TPPBx) in 5 weeks’ time. Methods Fifteen patients with elevated serum prostate-specific antigen (PSA) were recruited to provide pre-antibiotic and post-antibiotic fecal samples. The V4 region of 16S rRNA was sequenced. Analysis was performed by QIIME2. Alpha- and beta-diversities were analyzed, as well as the differential enrichment by Linear discriminant analysis Effect Size (LEfSe) analysis. Results Both the alpha- and beta-diversities of the pre- and post-antibiotic fecal samples were significantly different. Genera that are associated with alleviation of inflammation were enriched in the pre-antibiotic fecal samples, while the inflammation-associated genera were more enriched in the post-antibiotic fecal samples. Conclusion A single dose of oral co-amoxiclav before TPPBx could have led to a change of gut microbiota that cannot be recovered in 5 weeks' time. Microbiome studies on prostate cancer patients should be cautioned on the use of post-prostate biopsy fecal sampling. Further studies should be conducted for the impact on gut microbiome for TPPBx alone.